2013
DOI: 10.1016/j.ijantimicag.2013.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Challenging the concept of bacteria subsisting on antibiotics

Abstract: a b s t r a c tAntibiotic resistance concerns have been compounded by a report that soil bacteria can catabolise antibiotics, i.e. break down and use them as a sole carbon source. To date this has not been verified or reproduced, therefore in this study soil bacteria were screened to verify and reproduce this hypothesis. Survival in high concentrations of antibiotics was initially observed; however, on further analysis these bacteria either did not degrade the antibiotics or they used an intrinsic resistance m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 20 publications
3
15
0
Order By: Relevance
“…Previously, Walsh et al (2013) tried to reproduce and verify the hypothesis that soil bacteria are capable to subsist on antibiotics that was brought forwards by Dantas et al (2008). Similar to our results, Walsh and coworkers found that soil bacteria were not able to degrade antibiotics and as a consequence, it is unlikely to be used as a carbon source.…”
Section: Subsistence Phenotype: An Ecological Contextsupporting
confidence: 86%
See 3 more Smart Citations
“…Previously, Walsh et al (2013) tried to reproduce and verify the hypothesis that soil bacteria are capable to subsist on antibiotics that was brought forwards by Dantas et al (2008). Similar to our results, Walsh and coworkers found that soil bacteria were not able to degrade antibiotics and as a consequence, it is unlikely to be used as a carbon source.…”
Section: Subsistence Phenotype: An Ecological Contextsupporting
confidence: 86%
“…Alternatively, Walsh et al (2013) proposed that bacteria possibly use a well characterized resistance mechanism that has not been previously linked to antibiotic subsistence.…”
Section: Subsistence Phenotype: An Ecological Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…Although antimicrobial compounds can inhibit or kill other strains competing for the same ecological niche, in rare cases it has been shown that antibiotics can act also as a source of nutrients promoting the growth of bacteria under nutrient deprived conditions (D'Costa et al, 2006;Dantas et al, 2008). However, contrary to the findings by Dantas a study done by Walsh and co-workers was not able to confirm the previous findings, thus it is still questionable if antibiotics can act as a source of nutrients (Walsh et al, 2013). Hence, there is so far no scientific consensus on the ecological role of antimicrobial compounds in nature (Figure 1.1).…”
Section: Competitive Strategies Of Soil Microbesmentioning
confidence: 81%